Consumer Attitudes Toward Food and Nutritional Labeling: Implications for Policymakers and Practitioners on a National Level - Gomes, S (2020)
This paper investigates how consumers use and understand nutrition information on food labels in their daily lives. Primary data were collected from a survey (1127 Portuguese consumers) and four focus groups exploring dissimilarities among consumer segments: a) nutrition-concerned adults; b) adults non-concerned with nutritional issues; c) young consumers, aged 15-18; d) less educated and older consumers. A mixed-methods approach was crucial to further understand consumers' preferences for labels and to identify obstacles to their use. Data evidence that consumers prefer symbolic, coloured, and simple, FOP schemes and that 'traffic light' schemes are better understood and result in faster decision-making at points of sale. By collecting data on how different consumer segments search, understand, like, and use food labels, this paper provides rich guidelines to agri-food practitioners' future actions, particularly retailers. It also reveals serious interpretation obstacles faced by consumers, which needs to be revisited by policy-makers on nutritional labelling and inform decisions on a national scheme. Lastly, it further strengthens existing models by setting that some influencing dimensions are related to the idiosyncratic nature of the subject (consumer) and others are related to the object itself (label format), neither of which has been explored in the literature.